IMPACTO DAS MUDANÇAS CLIMÁTICAS NA DISTRIBUIÇÃO DE Libidibia paraguariensis (D. PARODI) G. P. LEWIS, UMA ESPÉCIE ARBÓREA ENDÊMICA DO CHACO - CARDINAL, Renan Henrique Silvestre; SARTORI, Angela Lúcia Bagnatori; TOMAZINI, Rita Cassiana Molmelstet; RIVABEN, Rodrigo Cyrino; PONTARA, Vanessa; BUENO, Marcelo Leandro (ANAIS DO ENIC, 2025)
-